Beta Regression Models: Joint Mean and Variance Modeling (2015)
In this paper joint mean and variance beta regression models are proposed. The proposed models are fitted applying Bayesian methodology and assuming normal prior distribution for the regression parameters. An analysis of structural and real data is included, assuming the proposed model, together with a comparison of the result obtained assuming joint modeling of the mean and precision parameters.